2015
DOI: 10.1016/j.amepre.2014.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Diabetes Health Policies Using Natural Experiments

Abstract: The high prevalence and costs of type 2 diabetes makes it a rapidly evolving focus of policy action. Health systems, employers, community organizations, and public agencies have increasingly looked to translate the benefits of promising research interventions into innovative polices intended to prevent or control diabetes. Though guided by research, these health policies provide no guarantee of effectiveness and may have opportunity costs or unintended consequences. Natural experiments use pragmatic and availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 37 publications
0
17
0
Order By: Relevance
“…All NEXT-D studies are evaluations of 'naturally' occurring health polices and/or interventions (ie, without randomization), using the strongest observational research designs possible and conducted in close collaboration with organizations implementing those programs. [11][12][13] The academic team members analyzed all data independently and retained sole authority over all publication-related decisions throughout the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…All NEXT-D studies are evaluations of 'naturally' occurring health polices and/or interventions (ie, without randomization), using the strongest observational research designs possible and conducted in close collaboration with organizations implementing those programs. [11][12][13] The academic team members analyzed all data independently and retained sole authority over all publication-related decisions throughout the course of the study.…”
Section: Methodsmentioning
confidence: 99%
“…However, our review of the literature also found that there are a limited number of published evaluations of specific diabetes population care approaches, and those that are published may not have the level of programmatic detail required for dissemination into other settings. Future research in this area should continue to identify, rigorously evaluate, and publish results from high quality ‘natural experiments’ in diabetes population care management 45 .…”
Section: Recommendations For Future Research and Policymentioning
confidence: 99%
“…Research typically follows a slower timeline, whereas program changes may occur more rapidly and/or in real-time. This tension is exacerbated by research funding being more available for traditional clinical trials that focus on testing interventions in relatively controlled circumstances rather than assessing effectiveness and implementation approaches in less controlled real-world settings [69]. Frenk (1992) and others have described this tension as navigating trade-offs between scientific excellence (contributing to internal validity) versus being relevant, responsive, and timely (contributing to external validity) [4, 5, 1013].…”
Section: Introductionmentioning
confidence: 99%